Prosocial Behavior of Boarding and Non-Boarding Students: A Comparative Analysis in the Context of Religious Higher Education - Novi Rosita Rahmawati; Desy Zukhrufia Rahma; Lilla Maturizka Ayu Asfarina; Maziyyatul Muslimah (Program Studi Bimbingan dan Konseling Islam, 2026)
Prosocial behavior is an important indicator of students' social development and is often assumed to be influenced by their residential environment. This study aims to examine the differences in prosocial behavior between boarding and non-boarding students in the Islamic Religious Education Study Program at UIN Syekh Wasil Kediri. Boarding in this study refers to students living in Islamic boarding schools or religious dormitories. The study used a comparative, quantitative approach with a sample of 224 students, comprising 112 boarding and 112 non-boarding students. Data were collected using a prosocial behavior scale and analyzed using an independent samples t-test. The results showed no significant differences in prosocial behavior between boarding and non-boarding students. The small effect size indicates that residential status is not strong enough to explain variations in students' prosocial behavior. These findings emphasize that prosocial behavior needs to be understood in terms of the quality of social experiences, relational support, and the internalization of values, rather than solely in terms of residential category.